USING THE "ANCHOR" METHOD IN TEACHING FOREIGN LANGUAGES IN INCLUSIVE EDUCATION: UZBEKISTAN CASE - Saodat Agzamkhodjaeva; Dr. Ahmad Juma Khatib (Bright Mind Publishing, 2025)
This study presents an original analysis of the application of the Anchor method as an affect-sensitive pedagogical approach in teaching foreign languages within inclusive education settings in Uzbekistan. The research is grounded in classroom-based empirical data and does not reproduce or replicate previously published texts. Using a mixed-methods case study design, the study examines how emotionally and sensory grounded anchors—such as gestures, routines, personal associations, and visual–tactile cues—support learner engagement, vocabulary retention, and communicative confidence among students with and without special educational needs (SEN). Data were collected from three inclusive secondary schools through pre- and post-intervention vocabulary assessments, systematic classroom observations, teacher interviews, and student focus groups. The findings demonstrate statistically significant improvements in receptive and productive vocabulary acquisition, increased participation rates, and reduced classroom anxiety, particularly among learners with SEN. The results suggest that the Anchor method contributes to lowering affective barriers and promoting equitable participation in foreign language classrooms. The article discusses pedagogical implications for inclusive language teaching in resource-constrained contexts and offers recommendations for sustainable implementation aligned with Uzbekistan’s inclusive education reforms.
Keywords: Anchor method; inclusive education; foreign language teaching; emotional anchoring; special educational needs; Uzbekistan; second language acquisition.